Design of switch curves geometry - D. S. Ershov (Вестник Научно-исследовательского института железнодорожного транспорта, 2025)
Introduction. In addition to ensuring reliability and safety, special attention should be paid to meeting the speed requirements of railway rolling stock in main lines in designing switch devices. Constructive solutions of switch facilities are determined by indicators of the dynamics of rolling stock when railway crews move along the track. According to the author, the design methods of switch curves do not meet modern speed requirements of rolling stock. The purpose of this article is to develop new approaches to the design of switch curves.Materials and methods. The author applied analysis method of dynamic and kinematic parameters of applied switch curves used in turnout switches constructions. Tensometric methods of the investigated parameters of turnout switches are obtained.Results. The analysis of turnout switch design methods is performed. Operational tests of the turnout switch with improved dynamic and kinematic characteristics were performed. The obtained results indicate the expediency of improving the design methodology of switch curves, the effectiveness of using geometric schemes of switch switches with tangential geometry.Discussion and conclusion. Comparative operational tests of turnout switches with the tangential and secant shapes of the switch curve proposed in the article show that the service life of the curved contact tongues increased. It is relevant to conduct similar tests with other types of turnout switches. Considering the results of tests and calculations, the next stage is planned to address the issue of adjusting the design methods of turnout switches products, especially for high-speed trafﬁc.